An experimental investigation of aeration performance in stepped spillways - Baylar, A; Emiroglu, ME; Bagatur, T (Wiley, 2006)
Dissolved oxygen content is a prime indicator of water quality. The oxygen transfer across the air-water interface at a hydraulic structure, such as a weir or spillway, occurs by self-aeration along the chute and by flow aeration in the hydraulic jump at the downstream end of the structure. Despite increased research activities in the field of stepped spillways, the aeration efficiency of stepped spillways is not yet known. This paper investigates the aeration efficiency of stepped spillways, in particular the effects of varying chute angle and step height. Empirical correlations predicting length of the nonaerated flow region and aeration efficiency were developed. The results indicate that stepped spillways are effective for oxygen transfer.
Keywords: aeration performance; dissolved oxygen; nappe flow; oxygen transfer; skimming flow; stepped spillway; transition flow